Superconductivity of lanthanum hydride synthesized using AlH3 as a hydrogen source. (24th September 2020) - Sakata, Masafumi; Einaga, Mari; Dezhong, Meng; Sato, Toyoto; Orimo, Shin-ichi; Shimizu, Katsuya
Abstract: Hydrogen-rich compounds show high- T c superconductivity related to dense hydrogen under extremely high pressure (above 100 GPa). A recent investigation to search for high- T c superconductive hydrides has advanced a synthesis technique using infrared laser heating of a hydrogen source material under conditions of extremely high pressure and temperature. In order to find a suitable synthesis route for high- T c superconductive hydrides, the selection of a hydrogen source material has to be considered. In this study, the synthesis of hydrogen-rich lanthanum hydrides (LaH x ) was performed using aluminium trihydride (AlH3 ) as the hydrogen source. Simple lanthanum on AlH3 was pressurized at 150 GPa and heated by infrared laser irradiation. After the laser heating, superconductivity at T c ∼ 70 K was observed at 170 GPa. This indicates that LaH x (x < 10) was synthesized using AlH3 as the hydrogen source under conditions of extremely high pressure.